Analisis Kejadian Stunting pada Balita Ditinjau dari Pengetahuan Ibu di Wilayah Kerja Puskesmas Sigompul Kabupaten Humbang Hasundutan - Rosmiaty Silaban; Martina Ariani; Lasria Simamora (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Approximately 151 million children under the age of five are stunted worldwide, with 55% of stunted children living in Asia and 39% of stunted children living in Africa. Based on the Basic Health Research Data (Riskdas), the prevalence of stunting in Indonesia increased to 36.8% in 2007, 35.6% in 2010, and 37.2% in 2013. Of this number, 18% were very short and 19.2% were short. Based on the 2018 Riskesdas data, the prevalence of stunted babies in Indonesia was 30.8%. Based on the 2019 Indonesian Child Nutrition Survey data, the situation in Indonesia is still relatively high, with a stunting prevalence of 27.67%. This figure shows that the stunting rate in Indonesia is still higher than in Southeast Asia at 24.7%. The results of the study showed that pregnant women's knowledge due to stunting, with an odds ratio of 9.1 (1.99–41.44), with a p value of 0.007 <0.05. To prevent stunting, an integrated and multisectoral program is needed to increase maternal awareness of child nutrition.